Cefuroxime, a New Cephalosporin Antibiotic: Activity In Vitro - O'Callaghan, Cynthia H. (1976)
Cefuroxime is a new broad-spectrum cephalosporin antibiotic with increased stability to β-lactamases. This stability, although no absolute in all cases, has the effect of widening the antibacterial spectrum of the compound so that many organisms resistant to the established cephalosporins are susceptible to cefuroxime. It is active against gram-positive organisms, including penicillinase-producing staphylococci, but it is less active against methicillin-resistant strains. In addition to its high activity against non-β-lactamase-producing gram-negative bacteria, cefuroxime effectively inhibits the growth of many β-lactamase-producing strains, including Enterobacter, Klebsiella, and indole-positive Proteus spp. It is highly active against Neisseria gonorrhoeae, Neisseria meningitidis, and also Haemophilus influenzae, including ampicillin-resistant strains. Cefuroxime is rapidly bactericidal and induces the formation and subsequent lysis of filamentous forms over a small concentration range.